Relationship between body composition and swimming performance in competitive junior swimmers - Nishimura, T.; Kumahara, H.; Touda, M.; Sasaki, A.; Yamato, T. (The Journal of Physical Fitness and Sports Medicine, 2017)
[Aims] This study aimed to evaluate the relationship between body composition and swimming performance in Japanese junior swimmers through five different events. [Methods] This cross-sectional study involved 79 males and 70 females (11-18 yrs). The percent body fat (%FAT) was assessed by skin-fold technique, from which lean body mass (LBM) and LBM index (LBMI) were determined. The swimming performance (%R) of the participants was evaluated as follows: the personal best time in recent competitive events divided by the categorized time (15 levels), as set by the Japan Swimming Federation. [Results] A stepwise multiple regression analysis revealed that LBM was the main single determinant for %R in the front crawl, backstroke and individual medley in males, accounting for 71%-96% of the total variance. Moreover, LBMI and the months-duration of competitive swimming career (MSC) were significant determinants of %R in the breaststroke, accounting for 76% of the variance. In contrast, MSC was the single determinant of %R in the butterfly, accounting for 41% of the variance. In females, LBM was a significant determinant in the front crawl and butterfly, whereas height and height plus %FAT determined %R in the backstroke and breaststroke, respectively. [Conclusions] These results indicate that LBM is the key predictor of performance through four swimming events in Japanese junior male swimmers. However, the result differs in female swimmers, suggesting that the effect of body composition profile on %R might depend on the swimming event.